Surface cross-equatorial pathways of seawater from the Bay of Bengal - Zhang, Zhengbei; Wang, Jing; Hao, Jiajia; Yuan, Dongliang; Wang, Kunxiang (Frontiers in Marine Science, 2023)
Cross-equatorial pathways of heat and salt in the Eastern Indian Ocean are analyzed using Lagrangian trajectories based on the ECCO2 model simulation and drifter-derived currents combined with Argo data. The results show that most of the particles released in the Bay of Bengal move across the equator near the eastern boundary of the upper Indian Ocean (< 50m) during the southwest monsoon season and join in the South Equatorial Current of the wind-driven circulation. Meridional salt and heat transports associated with the cross-equatorial currents feature significant seasonal variations, with stronger southward transports during the southwest monsoon than northward transports during the northeast monsoon, which are correlated significantly with the surface Ekman transports. The estimated annual mean salt and heat transports, based on the model (observational) data, are -0.06×10^9 (-0.11×10^9) kg·s-1 and -0.20 (-0.38) PW (1PW = 1015 W), respectively, southward across the equator.